Detailed long-term dynamics of neutrophil-to-lymphocyte ratio under biologic treatment reveal differential effects of tumour necrosis factor-alpha and interleukin 12/23 antagonists - Hoffmann, Jochen; Knoop, Christian; Enk, Alexander; Hadaschik, Eva (Acta dermato-venereologica, 2021)
Psoriasis is thought to be associated with a reduced life expectancy through systemic inflammation. A comparative, retrospective analysis of neutrophil-to-lympho-cyte ratio, a biomarker of systemic inflammation and cardiovascular risk, under 196 treatments with tumour necrosis factor-α and interleukin-12/23 antagonists was performed. Neutrophil-to-lympho-cyte ratio decreased significantly within 3 months of initiation of treatment and remained stable at reduced levels for at least 33 months. Dynamics were more pronounced and neutrophil-to-lympho-cyte ratio under treatment was lower in patients treated with tumour necrosis factor-α compared with interleukin-12/23 antagonists (geometric mean (95% confidence interval): 2.03 (1.9, 2.1) vs 2.63 (2.2, 3.2), respectively, p = 0.014). tumour necrosis factor-α antagonist treatment and baseline neutrophil-to-lympho-cyte ratio were independent predictors of a median low cardiovascular risk neutrophil-to-lympho-cyte ratio (< 2.15) during treatment (odds ratio (95% confidence interval): 0.53 (0.4-0.8) and 4.68 (1.0-19.1), p = 0.001 and p = 0.032, respectively). These results demonstrate a rapid and sustained reduction in biomarkers of systemic inflammation under biologic treatment. Furthermore, these data suggest class-specific effects on systemic inflammation, which may be relevant for the prevention of psoriasis co-morbidity by systemic treatment.